MAP4K3/GLK Promotes Lung Cancer Metastasis by Phosphorylating and Activating IQGAP1 - Chuang, Huai-Chia; Chang, Chih-Chi; Teng, Chiao-Fang; Hsueh, Chia-Hsin; Chiu, Li-Li; Hsu, Pu-Ming; Lee, Ming-Ching; Hsu, Chung-Ping; Chen, Yi-Rong; Liu, Yi-Chung; Lyu, Ping-Chiang; Tan, Tse-Hua (Cancer research (Chicago, Ill.), 2019)
Overexpression of the serine/threonine kinase GLK/MAP4K3 in human lung cancer is associated with poor prognosis and recurrence, however, the role of GLK in cancer recurrence remains unclear. Here, we report that transgenic GLK promotes tumor metastasis and cell migration through the scaffold protein IQ motif-containing GTPase-activating protein 1(IQGAP1). GLK transgenic mice displayed enhanced distant metastasis. IQGAP1 was identified as a GLK-interacting protein; two proline-rich regions of GLK and the WW domain of IQGAP1 mediated this interaction. GLK and IQGAP1 colocalized at the leading edge including filopodia and lamellipodia of migrating cells. GLK directly phosphorylated IQGAP1 at Ser-480 enhancing Cdc42 activation and subsequent cell migration. GLK-induced cell migration and lung cancer metastasis were abolished by IQGAP1 depletion. Consistently, human NSCLC patient tissues displayed increased phospho-IQGAP1, which correlated with poor survival. Collectively, GLK promotes lung cancer metastasis by binding to, phosphorylating, and activating IQGAP1. SIGNIFICANCE: These findings show the critical role of the GLK-IQGAP cascade in cell migration and tumor metastasis, suggesting it as a potential biomarker and therapeutic target for lung cancer recurrence.